Phytoplankton light absorption in the deep chlorophyll maximum layer of the Black Sea. (28th March 2019) - Churilova, T.; Suslin, V.; Sosik, H.M.; Efimova, T.; Moiseeva, N.; Moncheva, S.; Mukhanov, V.; Rylkova, O.; Krivenko, O.
ABSTRACT: Bio-optical data, obtained during six cruises in the Black Sea carried out during periods of seasonal stratification in years between 1996 and 2016, have been used to parametrize phytoplankton light absorption (a p h λ ) in the deep chlorophyll maximum (DCM) layer located near the bottom of euphotic zone. Relationships betweena p h λ and the sum of chlorophyll- a and phaeopigment concentrations (Chl- a ) differed from those for the summertime upper mixed layer (UML). Notably, chlorophyll a specific absorption coefficients (a p h ∗ λ ) were lower in the DCM and more comparable witha p h ∗ λ values typical for winter phytoplankton in the Black Sea. Thea p h λ spectral shapes in the DCM differed markedly from those in winter and in the summer UML, due to a shoulder at 490 nm and a local maximum at 550 nm corresponding to the absorption bands of phycourobilin and phycoerythrobilin. Light absorbing properties of phytoplankton in the DCM (amplitude and spectral shape ofa p h ∗ λ ) reflected physiological acclimation to local conditions on the cellular level and population shifts leading to changes in the biomass-dominant species, with Synechococcus spp. domination in the DCM. The parameterization of phytoplankton absorption in the DCM will enable refined spectral models of the downwelling radiance and primary production in the Black Sea.